Differences in Salmonella Serovars Response to Lactic Acid and Peracetic Acid Treatment Applied to Pork - Mariana Fernandez; Alexandra Calle (Journal of Food Protection)
Pathogen control in the meat industry relies on the effectiveness of postharvest interventions in reducing microbial populations. This study investigated differences in the survival of Salmonella serovars when exposed to organic acids used as antimicrobials on raw pork meat. Seven serovars were included in this study (S. Newport, S. Kentucky, S. Typhimurium, S. Dublin, S. Heidelberg, S. Infantis, and S. Enteritidis). Multistrain serovar cocktails were prepared and tested against lactic acid (LA) and peracetic acid PAA at two concentrations, LA 2 and 4% and PAA 200 and 400 ppm. Pork samples were assigned to each serovar, inoculated with 6.0 Log CFU/cm2 Salmonella (one serovar at a time), and treated with the corresponding antimicrobials. A two-way analysis of variance was conducted to examine the effects of serovar and antimicrobial concentrations on Salmonella survival. A significant main effect of serovar was identified, indicating that Salmonella concentration and reduction rate were significantly affected by serovar. Similarly, a significant main effect of antimicrobials was observed, suggesting that the treatment types impacted Salmonella concentration and reduction rate. However, the interaction effect between serovar and antimicrobial was not significant. Posthoc comparisons indicate that PAA 400 ppm is more effective at reducing Salmonella concentrations and that S. Dublin may be more susceptible than S. Newport to antimicrobial sprays. Additionally, under PAA exposure, only S. Dublin, S. Kentucky, and S. Heidelberg showed statistically significant differences (P < 0.05) compared with the control, indicating that these three serovars are more susceptible to PAA treatments than the rest. The behavior of different Salmonella serovars under stress conditions can give us an insight into how these pathogens survive processing.